Mammographic parameters as predictors of molecular subtype of breast cancer: a prospective analysis - Nidhi Rana; Shruti Thakur; Vijay Thakur; Arun Chauhan; Anchana Gulati; Sushma Makhaik (Surgical and Experimental Pathology)
Abstract Background The prevalence of breast cancer is increasing globally and its early detection is the need of hour for giving the patient a long disease-free meaningful life. The latest management regimes depend upon the biological behavior of the breast cancer that itself relies upon expression of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (Her 2) neu status for its molecular subtyping. Aim To determine the predictive value of mammographic parameters in identifying the estrogen and progesterone hormone receptor status, human epidermal growth factor receptor 2 (Her 2) neu expression and molecular subtypes of breast cancer. Methods A prospective observational study was conducted from January 2021 to September 2022 in a tertiary care institute. The study enrolled 51 females with histopathologically proven invasive breast carcinoma. The patients underwent digital mammography followed by tissue biopsy. Mammographic parameters were based on Breast Imaging-Reporting and Data System (BI-RADS) imaging features. The molecular subtypes of breast cancer were grouped into four subtypes based on St. Gallen International Expert Consensus Panel 2013. The mammographic features were then statistically correlated with molecular subtypes of breast cancer. Results Luminal type A was the most common molecular subtype in our study [ 17 (33.33%)] followed by triple negative type [10(19.61%)]. Tumors with non-circumscribed margins were predicted to be Luminal A or Luminal B subtype (p value < 0.02). Tumor with microcalcification was strongly predicted to be Her 2 subtype with a statistically significant association (p value < 0.001). Circumscribed tumors with absence of microcalcification were predicted to be triple-negative type of breast cancer. Conclusions Key features in mammography were significantly associated with breast cancer molecular subtypes. Knowledge of such correlations could help clinicians stratify breast cancer patients according to their likely molecular subtypes, potentially enabling earlier, more effective treatment or aiding in therapeutic decisions in countries where immunohistochemical (IHC) hormone receptor and Her 2 testing is not readily available.